A lignin-epoxy resin derived from biomass as an alternative to formaldehyde-based wood adhesives. Issue 7 (12th March 2018) - Li, Russell Jingxian; Gutierrez, Jose; Chung, Yi-Lin; Frank, Curtis W.; Billington, Sarah L.; Sattely, Elizabeth S.
Abstract : Wood products are extensively used to make furniture items and construction materials; however, the majority contain formaldehyde-based adhesives that raise serious health concerns. Abstract : Wood products are extensively used to make furniture items and construction materials; however, the majority contain formaldehyde-based adhesives that raise serious health concerns. Here, we report a formaldehyde-free adhesive formulation comprised of two high-volume biorefinery biproducts, namely Kraft lignin (pulp and paper) and glycerol (biodiesel), and its adhesion properties as determined by ultimate shear stress as well as wood failure rates. We show that this lignin-based resin displays the same desirable characteristics as formaldehyde-based resins including water-tolerance, fast curing, and comparable adhesion performance. Chemical analysis indicates that resin curing occurs uncatalyzed via formation of ether bonds between lignin hydroxyl groups and the glycerol-derived crosslinker epoxide. We also show that different lignin and crosslinker feedstocks can be used in the formulation, in some cases with water as a cosolvent, to generate a set of lignin-derived resins with similar properties and mechanical strength. In contrast to the majority of formaldehyde-free adhesives, this lignin-epoxy formulation does not require the use of caustic base and known carcinogens. Furthermore, we demonstrate through mechanical testing and attention to processing conditions that this lignin-based resin has the potential to be a viable alternative to widely used formaldehyde resins.